(untitled) (Philological Studies, 2019)
The research of the Macedonian textile ornaments special interest causes circular motif „saan“, which is ornamented festive women’s shirt "saani" and "simidinata" from the region of Skopska Blatija and Skopsko. In the Macedonian dialect language whit the term "saan" are appointed all large shallow metal vessels or bowls. This meaning is almost identical to the Turkish word "saxan" (mak. saan), which indicates shallow copper bowl. Phonetic closeness of the Turkish word sahan with "saéna" (avest. Maraγō saēnō), the word from the Avestal language (a group of ancient Iranian languages) indicates the possibility of etymological origin of the word. This words has a similar meaning in ancient-Aryan and Iranian culture, which represents the mythological giant bird - Simurg or fantastic creature Senmur. The appearance of ornithology motives, mentioned in embroidery and belt buckles that are attached to the character of the mythical snake or bird of folk oral tradition, leads to the conclusion that it is an ancient model with common semiotic code, present in traditional culture among most nations of indo-еuropean areal.